Prophetic Learning Methods in Shaping Inclusive-Religious Islamic Education for Santri with Special Needs - Asrori, Muhammad; Albab , Hayyan Ahmad Ulul (Journal of Education and Religious Studies, 2023)
This article aimed to describe the content, teachings, and patterns of hiwar hadiths in the book Al-Arbain Al-Nawawiyah that contribute to shaping an inclusive Islamic education. The hiwar hadiths in this book can be used as a basis for forming inclusive Islamic education. The study was carried out using a qualitative approach and library study. Researchers collected data from primary sources, including Al-Arbain Al-Nawawiyah and its explanatory texts (syarh). Additionally, relevant articles were consulted to support the analysis. The findings indicated that ten hadiths in Al-Arbain Al-Nawawiyah incorporate the hiwar method. These hadiths cover topics related to faith (iman), fundamental Islamic teachings, and ethics. They also highlight the Prophet Muhammad’s frequent use of hiwar as a teaching method to convey Islamic principles to his companions. The study further emphasized that the hiwar method plays a crucial role in fostering an inclusive mindset among santri. By prioritizing the hiwar approach in teaching Islamic religious education, this study can serve as a reference for developing a more inclusive education system.